Coexistência de DPOC e SAOS : impacto na variabilidade da frequência cardíaca e na capacidade funcional - Zangrando, Katiany Thays Lopes (2017)
Several studies have investigated the deleterious effects of the association between the chronic obstructive pulmonary disease (COPD) and obstructive sleep apnea syndrome (OSAS), however, it is still unknown whether coexistence of COPD and OSAS ("OLDOSA") is associated to greater autonomic impairment, as well as, whether the changes triggered by overlap disease are associated with greater functional impairment for this population. Thus, a study titled "Severity of COPD and its association with OSAS: impact on autonomic modulation and functional capacity" was carried out with the purpose of evaluating whether this coexistence would imply greater autonomic impairment and functional capacity than when presented in the COPD conditions in isolation. In the present study, the heart rate variability indexes (HRV) of twenty four individuals with COPD (n=12) and OLDOSA (n=12) were evaluated by means of electrocardiographic recording during rest, active posture maneuver (APM), respiratory sinus arrhythmia maneuver (RSA-m) and six-minute walk test (6MWT). Our results showed that the COPD group presented higher parasympathetic modulation during APM in contrast to the OLDOSA group (p = 0.02). In contrast, the OLDOSA group had marked sympathetic modulation during RSA-m when compared to the COPD group (p = 0.00). Additionally, the exercise performance during the walking test was similarly impaired in both groups despite the greater severity of the COPD group. Therefore, our results suggest patients with OLDOSA coexistence have marked sympathetic modulation, and the presence of OSAS in COPD patients has a negative impact on functional capacity regardless of the severity of the lung disease.